Measuring Chinese English-as-a-foreign-language learners’ resilience: Development and validation of the foreign language learning resilience scale - Guo, Nianyu; Li, Rui (Frontiers in Psychology, 2022)
Despite the growing body of research on the factors of resilience in diverse fields, there is still a dearth of particular attention on foreign language learning resilience. To fill the gap, this study seeks to develop the Foreign Language Learning Resilience Scale to measure its psychometric scale reliability and validity in Chinese English-as-a-foreign-language contexts. Valid data were collected from 313 Chinese English-as-a-foreign-language college students who voluntarily participated in the survey. The Foreign Language Learning Resilience Scale was validated based on a series of reliability (e.g., item analysis, split-half reliability and internal consistency) and validity (e.g., construct validity, convergent validity and discriminant validity) tests. Results suggested that the 19-item Foreign Language Learning Resilience Scale presented three factors: ego resilience, metacognitive resilience and social resilience. Besides, all the three factors contributed high effects to foreign language learning resilience. Among the three factors, metacognitive resilience was found to have the highest path coefficient, followed by social resilience, with ego resilience having the lowest. The validated scale could advance knowledge in the field of second language acquisition regarding how learners’ individual differences, emotional factors and the contextual antecedents may affect foreign language learning resilience.